2021
DOI: 10.1002/hep.31524
|View full text |Cite
|
Sign up to set email alerts
|

Activated Protein Phosphatase 2A Disrupts Nutrient Sensing Balance Between Mechanistic Target of Rapamycin Complex 1 and Adenosine Monophosphate–Activated Protein Kinase, Causing Sarcopenia in Alcohol‐Associated Liver Disease

Abstract: BaCKgRoUND aND aIMS: Despite the high clinical significance of sarcopenia in alcohol-associated cirrhosis, there are currently no effective therapies because the underlying mechanisms are poorly understood. We determined the mechanisms of ethanol-induced impaired phosphorylation of mechanistic target of rapamycin complex 1 (mTORC1) and adenosine monophosphate-activated protein kinase (AMPK) with consequent dysregulated skeletal muscle protein homeostasis (balance between protein synthesis and breakdown). appRo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 66 publications
3
19
0
Order By: Relevance
“…Metabolic intermediates in the TCA cycle were quantified in UnT, ammonia-treated, and after ammonia withdrawal myotubes and gastrocnemius muscle from PCA and sham-operated rats using methods previously reported (42). JCI Insight 2021;6(24):e154089 https://doi.org/10.1172/jci.insight.154089…”
Section: Targeted Metabolomicsmentioning
confidence: 99%
“…Metabolic intermediates in the TCA cycle were quantified in UnT, ammonia-treated, and after ammonia withdrawal myotubes and gastrocnemius muscle from PCA and sham-operated rats using methods previously reported (42). JCI Insight 2021;6(24):e154089 https://doi.org/10.1172/jci.insight.154089…”
Section: Targeted Metabolomicsmentioning
confidence: 99%
“…In addition, the biological functions of the identified DEGs were examined. Although plenty of studies demonstrated that alcohol influences gene expression in the liver and kidney, 29,30 the alcohol content in each EC treatment group in the current study was the same, resulting in similar effects on gene expression. Thus, the effect of alcohol can be excluded.…”
Section: Discussionmentioning
confidence: 59%
“…( 38 ) Ethanol metabolism in the muscle contributes to decreased protein synthesis and increased autophagy proteolysis. ( 39‐41 ) Our metabolomics data showed an increase in the level of proteolysis markers, especially in those with DC.…”
Section: Discussionmentioning
confidence: 83%